2019
DOI: 10.3390/molecules24183266
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase Inhibition Antioxidant Effect and Cytotoxicity Studies of the Extracts of Cudrania tricuspidata Fruit Standardized in Chlorogenic Acid

Abstract: In the present study, various extracts of C. tricuspidata fruit were prepared with varying ethanol contents and evaluated for their biomarker and biological properties. The 80% ethanolic extract showed the best tyrosinase inhibitory activity, while the 100% ethanolic extract showed the best total phenolics and flavonoids contents. The HPLC method was applied to analyze the chlorogenic acid in C. tricuspidata fruit extracts. The results suggest that the observed antioxidant and tyrosinase inhibitory activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…Although chlorogenic acid does not have a significant direct inhibitory effect, its metabolites can inhibit melanogenesis in B16 melanoma cells by inhibiting tyrosinase activity. Oh et al [38] showed that ethanol extract has the best tyrosinase inhibitory activity, similar to the results of this study. The extracts with the best tyrosinase inhibitory activity in this study were No.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although chlorogenic acid does not have a significant direct inhibitory effect, its metabolites can inhibit melanogenesis in B16 melanoma cells by inhibiting tyrosinase activity. Oh et al [38] showed that ethanol extract has the best tyrosinase inhibitory activity, similar to the results of this study. The extracts with the best tyrosinase inhibitory activity in this study were No.…”
Section: Discussionsupporting
confidence: 91%
“…1, are suitable for development as whitening ingredients (Table 7). Chlorogenic acid has excellent antioxidant capacity [38,39]. Although chlorogenic acid does not have a significant direct inhibitory effect, its metabolites can inhibit melanogenesis in B16 melanoma cells by inhibiting tyrosinase activity.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the literature could ascertain, compounds from coffee have been reported to be effective enzyme inhibitors. For example, caffeine, chlorogenic and caffeic acids exhibited promising enzyme inhibitory effects in in vitro and in vivo studies [ 18 , 19 , 20 , 21 , 53 , 54 ]. In addition, we observed a low correlation between the total bioactive compounds and the enzyme inhibitory effects.…”
Section: Resultsmentioning
confidence: 99%
“…Curcuma longa (C. longa), a member of the Zingiberaceae family, has several biological effects such as anti-inflammation, hyperlipidemia inhibition, and gastroprotection [9][10][11][12] . Our group has also worked to develop safe anti-inflammatory drugs from natural products [13][14][15] . Previously, we reported the anti-inflammatory effect of A. hookeri but were unable to elucidate the exact mechanism of action involved in the effect 14 .…”
mentioning
confidence: 99%